STRATEGI KOMUNIKASI ORGANISASI DALAM PENGELOLAAN, KOHESIVITAS DAN KEBERHASILAN KERJASAMA DI ERA PANDEMI COVID - 19 : (Studi pada Unit Kegiatan Mahasiswa Universitas Pembangunan Nasional Band Veteran Jakarta) - Raja Timotius Arbesis, (2022)
The COVID - 19 pandemic is a global phenomenan that had given significant impact upon every aspect of the society's livelyhood. The government urgency in prohibiting any form of direct contact between individuals had changed the society's communication method. This in turn also influenced how organization operates on a daily basis. Management, cohesivity and cooperation success are one of the few things that is mainly influenced by the new COVID - 19 regulations. UBV Jakarta is one the few organization that had been severly influenced by the COVID - 19 regulations. As one of the few organization that stands upon the family principle, these changes manifested into new and unexpected problems that endangers the organization integrity. The sudden need of a reformed organizational communication strategy is in order, one that could stand the changes that the COVID - 19 pandemic regulation brings, one that is also effective in maintaining management, cohesivity and cooperation success stabilty during the COVID - 19 pandemic. This research uses the qualitative method with in - depth interview and observation as its main method of collecting data. In - depth interviews are executed with few organization managers that had significant importance in organizational communication strategy topic. This research utilized the classic organization theory of Scott, Golddhabber's concept of organizational communication and Effendy's communication strategy concept. This research had successfully proven the massive role that organizational communication strategy played in outspreading information within the scope of internal and external part of UBV Jakarta. This research also proves how and why UBV Jakarta's organizational communication strategy is an integral part of maintaining the stabilty of organization's management, cohesivity and cooperation success. It is concluded that the three main point of this research depends on UBV Jakarta's organizational communication strategy success. Keywords : Organizational communication strategy; COVID - 19; Management